Geographic and Arts Education. Theoretical Foundations, Principles, Interfaces - Hofmann, Romy; Schubert, Jan Christoph (Journal of Geography Education, 2018)
There has been an increasing interest in Arts Education over the last decades. Arts Education includes practice-oriented and artistic-cultural activities of human beings. Its special potential lies in ’personal education’; it is assumed to develop learners’ senses, contribute to holistic and lifelong learning and lead to cultural participation. The paper starts by introducing brief conceptual overviews of education, aesthetics and culture along with central principles of Arts and Geographic Education. It outlines similarities and differences of both fields and finally elaborates hypotheses on the relation and future prospects in Geographic and Arts education that consider sensual-aesthetic dimensions in order to develop subject-specific education in a holistic way.